Physico-Mechanical Properties of Alkali-Activated Based Composites Using Recycled Tire Fibers - Edwin Gudiel; Jordi Payá; María Victoria Borrachero; José María Monzó (Applied Sciences)
Used tires (UTs) are a global problem, especially in developing countries due to inadequate management systems. During retreading, when the worn tread is replaced, waste is generated in the form of tire fibers (TFs) and particles, which can be reused as raw materials to produce economically and environmentally low-cost prefabricated elements. Using TFs as a lightweight aggregate in nonstructural geopolymer-based elements is a sustainable valorization option. This study aims to valorize used tires by incorporating them as TFs into lightweight geopolymer mixes and analyzing their physico-mechanical, thermal, and thermography properties for building and civil engineering applications. The geopolymer is produced from a precursor (spent catalyst residue from catalytic cracking, FCC) and an alkaline activator composed of rice husk ash (RHA), sodium hydroxide, and water. The control sample’s (mortar with siliceous sand, CTRLSIL) compressive strength came close to 50 MPa, while the TF mixes ranged from 32 to 3 MPa, which meet the masonry standards. The thermal conductivity and thermography analyses showed that increasing the TF content reduced the heat transmission and achieved a similar performance to expanded-clay concrete and better performance than for conventional concrete.